2019
DOI: 10.1200/po.18.00114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Durable Responses on Immune Checkpoint Inhibitors Versus Other Systemic Therapies: A Pooled Analysis of Phase III Trials

Abstract: PURPOSE Immune checkpoint inhibitors (ICIs) have been demonstrated to improve overall survival (OS) in several tumor types. Durable responses have been reported with these agents in patients with melanoma and lung cancer. We aimed to quantify the proportion of patients who experience durable responses on ICIs and to compare it with other drug classes. PATIENTS AND METHODS We retrieved published phase III randomized trials that included at least one ICI arm in the recurrent and/or metastatic setting. A durable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 27 publications
3
59
0
2
Order By: Relevance
“…In recent years, select subsets of patients have shown durable responses to immune checkpoint inhibitors [2][3][4]. Given the functional redundancies in immune checkpoints that exist, it is perhaps surprising that durable responses are observed with these single agents; but, it has been a welcome breakthrough nonetheless.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, select subsets of patients have shown durable responses to immune checkpoint inhibitors [2][3][4]. Given the functional redundancies in immune checkpoints that exist, it is perhaps surprising that durable responses are observed with these single agents; but, it has been a welcome breakthrough nonetheless.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, immunotherapy treatment has disrupted the management of these patients in the last few years, prolonging life expectancy and thus allowing surgical consolidation when needed. A recent review reported a life expectancy without cancer progression three time superior than the mean survival in all patients, compared to chemotherapy or targeted therapy [24]. Prophylactic fixation is recommended in cases of lytic metastases of the proximal femur presenting a Mirels' score superior or equal to 8 to quantify the risk of sustaining a pathological fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PD-L1 expression (defined as ≥1% tumor-infiltrating immune cells) had higher ORRs than those <1% (12% vs. 0%). After a median follow-up of 25.3 months, median duration of response was 21 months, which is very rare with cytotoxic agents in mTNBC but is often reported with ICIs in other solid tumors (11).…”
Section: Editorial Commentarymentioning
confidence: 91%